Urgensi Pemahaman Soteriologi bagi Pertumbuhan Spiritual Peserta Didik Agama Kristen di Era Kontemporer - Agresia, Dewita; Tapilaha, Sandra Rosiana (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2024)
This research examines the importance of understanding soteriology in the context of the growth of students' spiritual lives in the current era. In the midst of various spiritual challenges and rapid changes in times, a deep understanding of soteriology is an important foundation in strengthening faith, facing change, and encouraging healthy spiritual growth. Through literature study-based research, this research identifies the problem of lack of awareness of the importance of understanding soteriology among Christian religious students. This lack of understanding can cause a gap between the beliefs taught and the spiritual experiences felt by students. Therefore, this research emphasizes the importance for Christian religious educators to provide a learning environment that supports a deep understanding of soteriology. The learning environment in question includes the use of digital technology to provide interactive and relevant learning resources and encourage critical discussion and in-depth reflection on safety concepts. In conclusion, an understanding of soteriology plays a key role in shaping the growth of the spiritual life of Christian students. By strengthening this understanding through focused and in-depth Christian religious education, students can experience stronger spiritual growth and face spiritual challenges with greater confidence amidst the dynamics of the contemporary era.AbstrakPenelitian ini mengkaji pentingnya pemahaman soteriologi dalam konteks pertumbuhan kehidupan rohani peserta didik di era saat ini. Di tengah berbagai tantangan spiritual dan perubahan zaman yang cepat, pemahaman yang dalam tentang soteriologi menjadi landasan yang penting dalam memperkuat iman, menghadapi perubahan, dan mendorong pertumbuhan rohani yang sehat. Melalui penelitian berbasis studi pustaka, penelitian ini mengidentifikasi masalah kurangnya kesadaran akan pentingnya pemahaman tentang soteriologi di antara peserta didik agama Kristen. Kurangnya pemahaman ini dapat menyebabkan kesenjangan antara keyakinan yang diajarkan dan pengalaman rohani yang dirasakan oleh peserta didik. Oleh karena itu, penelitian ini menekankan pentingnya bagi pendidik agama Kristen untuk menyediakan lingkungan pembelajaran yang mendukung pemahaman yang mendalam tentang soteriologi. Lingkungan belajar yang dimaksud mencakup penggunaan teknologi digital untuk menyediakan sumber belajar yang interaktif dan relevan serta mendorong diskusi kritis dan refleksi mendalam tentang konsep keselamatan. Kesimpulannya, pemahaman tentang soteriologi memainkan peran kunci dalam membentuk pertumbuhan kehidupan rohani peserta didik agama Kristen. Dengan memperkuat pemahaman ini melalui pendidikan agama Kristen yang terarah dan mendalam, peserta didik dapat mengalami pertumbuhan rohani yang lebih kokoh dan menghadapi tantangan spiritual dengan keyakinan yang lebih mantap di tengah-tengah dinamika era kontemporer.